EEfecto de contaminantes sobre la transferencia de oxígeno en sistemas de aeración analizado mediante un modelo de dos zonas simplificado - Durán Herrera, Esteban (Universidad de Costa Rica, 2009)
A series of unsteady-state reaeration tests were performed in a 1000 l tank at 1-10-3 normal m3/s diffused-air flow rate and 298,65 K water temperature. Three different types of impurities: soybean oil, surfactant, and diatomaceous earth were doped to simulate the impurities in wastewaters and the effects of the impurities on the oxygen transfer rate were investigated. The ASCE and the new simplified two-zone oxygen mass-transfer models were used to analyze the unsteady-state reaeration data and the volumetric mass-transfer coefficients determined from them were correlated as a function of the impurity concentration. An empirical correlation that predicts successfully the volumetric oxygen-transfer coefficient in an aqueous system with mixed impurities was found. The results showed that the mass-transfer coefficients of the surface aeration zone are more sensitive to the impurity concentration than those of the gas bubble zone.